A SURVEY ON THE CURRENT PRACTICES OF SOFTWARE DEVELOPMENT PROCESS IN MALAYSIA (Journal of Information and Communication Technology, 2005)
Software quality is becoming increasingly important as our society becomes more dependent on computers. The required levels of quality are not likely to be achieved without giving proper attention to the software development process. Many studies regarding the practices of software development process have been carried out. The focus of these studies is mainly to examine the effectiveness of the practices. Most of studies were conducted in the United States, European countries, India, Japan and are very limited in Asian countries especially in Malaysia. In the view of that, we have carried out a study on the current practices of software development process in Malaysia. In this paper, we have analyzed and discussed the results found from the study. The structured questionnaire approach was used for data collection. The data was analyzed by using basic statistical techniques such as frequency and cross-tabulation. Theresults of this study have laid out some important points regarding the practices of the software development process in Malaysia. In addition, most of the practitioners were pursuing practices that have been traditionally used by the organizations. Lack of awareness in using good software development practices could be a key factor that contributes to the occurrence of quality problems in the organizations. Consequently, the results of this study have given us a good incentive to prolong our research in the area of software process certification.